2009
DOI: 10.1002/car.1064
|View full text |Cite
|
Sign up to set email alerts
|

‘Moved around like bags of rubbish nobody wants’: how multiple placement moves can make young women vulnerable to sexual exploitation

Abstract: This paper discusses fi ndings from an exploratory study that sought to identify how local authority care places young women at risk of sexual exploitation through prostitution by unpicking the 'culture of care', and focuses on frequent placement moves and the role of discontinuity. The author's experience of working with sexually exploited young women in local authority care, and women in street prostitution, provides a backdrop for the study. Findings are drawn from life story interviews with 14 young women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
71
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 16 publications
2
71
0
1
Order By: Relevance
“…The historic abuse of some female children and young people in this position has been highlighted by Coy (2009) in her survey of the literature on young women and care, who suggested that "young women who are currently looked after or have backgrounds of local authority care are significantly over-represented in prostitution in most major cities…similar findings are reported in Norway, Canada, and Australia" (p.255).…”
Section: Introductionmentioning
confidence: 95%
“…The historic abuse of some female children and young people in this position has been highlighted by Coy (2009) in her survey of the literature on young women and care, who suggested that "young women who are currently looked after or have backgrounds of local authority care are significantly over-represented in prostitution in most major cities…similar findings are reported in Norway, Canada, and Australia" (p.255).…”
Section: Introductionmentioning
confidence: 95%
“…Young females in residential care seem to be particularly at risk (Coy 2009) with a study in Northern Ireland indicating that over forty percent were at risk of sexually exploitation (Beckett, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…As children get older they become more mobile, come into contact with a wider social network and face a whole range of different social and environmental risks outside the family to younger children (Rees et al, 2010). Earlier maltreatment experiences and/or poor experiences of parenting during childhood and adolescence have often been shown to be linked to increased vulnerability and later risk taking behaviours, 3 such as running away, sexual exploitation, and substance misuse (Safe on the Streets Research Team, 1999;Bancroft et al, 2004;Rees and Lee, 2005;Smith et al, 2005;Thrane et al, 2006;Coy, 2009;Peled and Cohavi, 2009). Young people are also more likely to experience changes in family structure and this may play a part in terms of increased stress within families.…”
Section: Introductionmentioning
confidence: 99%
“…The review by Brandon et al (2009) highlights the difficulty for social workers of engaging with young people, often following on from negative experiences of care. Various commentators have highlighted that non-engagement of young people may be their way of actively taking some control of a situation in which their ability to assert choice is limited (Pearce 2006;McLeod, 2007;Coy, 2009). …”
Section: Introductionmentioning
confidence: 99%